BENEFITING FROM RUANGGURU FOR TEACHING ENGLISH: TEACHER’S PERSPECTIVE - Kamal Yusuf; Chalifia Rafidah (English Education Department, 2021)
Technology has been successfully attracting human’s life, including in education. It can be seen that there are a lot of online learning especially in English language learning that can be accessed by everyone in everywhere. In Indonesian context, Ruangguru is an example of an online course that most popular used nowadays. This paper aims at exploring the way of teaching practices that used by teachers and challenges they faced in teaching English in Ruangguru. This study is a descriptive qualitative using interview as the instrument of data. The respondents of this present study are teachers who teach English from different level of students and learning programs that were chosen by snowball sampling. This study found that most of the teachers have similar methods of teaching such as preparing materials reading and having knowledge before delivering lesson to students. The teachers also faced corresponding challenges such as internet connection and difficult question that should be answered directly.